2015
DOI: 10.1007/s00405-015-3545-5
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic classification of parapharyngeal space tumors: a case series and review of the literature

Abstract: The objective of the study is to present a large case series of parapharyngeal space tumors (PPST) and the most comprehensive literature review of tumor histopathologic distribution. The study was designed as internal case series and full Pubmed/MEDLINE electronic database review in a tertiary academic medical center. Tumor histopathology and patient demographics were obtained from a comprehensive Pubmed/MEDLINE database review, as well from an internal case series of 117 patients referred to our center betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…According to a systematic review by Riffat et al, tumors from up to 70 histological subtypes can be identified in the PPS (Table ). Approximately 80% of these tumors are benign and 20% malignant . Prestyloid tumors are more common (59%) than retrostyloid ones (26%); although, in some cases, it is difficult to determine the exact origin of the tumor (prestyloid/retrostyloid) (15%) .…”
Section: Pathologymentioning
confidence: 99%
See 4 more Smart Citations
“…According to a systematic review by Riffat et al, tumors from up to 70 histological subtypes can be identified in the PPS (Table ). Approximately 80% of these tumors are benign and 20% malignant . Prestyloid tumors are more common (59%) than retrostyloid ones (26%); although, in some cases, it is difficult to determine the exact origin of the tumor (prestyloid/retrostyloid) (15%) .…”
Section: Pathologymentioning
confidence: 99%
“…These global data come from recent studies of patients with PPS tumors . Different proportions can be found in some series.…”
Section: Pathologymentioning
confidence: 99%
See 3 more Smart Citations